2010
DOI: 10.1515/cclm.2010.006
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of errors in a clinical laboratory: a one-year experience

Abstract: Background: Efficient laboratory service is the cornerstone of modern health care systems. Scientific innovations have contributed to substantial improvements in the field of laboratory science, but errors still prevail. These errors are classified as preanalytical, analytical and postanalytical, depending upon the time of presentation. Methods: The data for 67,438 routine venous blood specimens were scrutinized, and errors were documented over the period of 1 year in the clinical biochemistry laboratory of Go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
66
4
11

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(88 citation statements)
references
References 13 publications
5
66
4
11
Order By: Relevance
“…10 Similarly, Goswami et al found that the pre-analytical errors were the most commonly encountered, with a frequency of 77.1% followed by post analytical accounting for 15% and analytical contributing upto 7.9% 11 In a survey on outpatient phlebotomy procedure, most unsuitable samples resulted from haemolysis (18.1%), insufficient quantity (16.0%), and clotting (13.4%) 12 These data are comparable to those provided by additional investigations, which confirm that problems directly related to specimen collection are the main causes of preanalytic errors, especially haemolysed, clotted, insufficient, and incorrect samples. [13][14][15][16] In our study, there was a high percentage of errors in the requisition slips.…”
Section: Discussionmentioning
confidence: 97%
“…10 Similarly, Goswami et al found that the pre-analytical errors were the most commonly encountered, with a frequency of 77.1% followed by post analytical accounting for 15% and analytical contributing upto 7.9% 11 In a survey on outpatient phlebotomy procedure, most unsuitable samples resulted from haemolysis (18.1%), insufficient quantity (16.0%), and clotting (13.4%) 12 These data are comparable to those provided by additional investigations, which confirm that problems directly related to specimen collection are the main causes of preanalytic errors, especially haemolysed, clotted, insufficient, and incorrect samples. [13][14][15][16] In our study, there was a high percentage of errors in the requisition slips.…”
Section: Discussionmentioning
confidence: 97%
“…Podemos observar que a etapa laboratorial com maior concentração de erros foi a fase pré-analítica. Goswami et al (11) coletaram dados durante um ano e tiveram alto índice de 77% de falhas nessa área. Os trabalhos de Plebani e Carraro (25) (6) …”
Section: Causas De Erros Descritas Nos Artigosunclassified
“…efisien ditandai oleh 3 hal yaitu presisi, akurat, dan Rerata TAT, standar deviasi, nilai maksimum dan minimum ketepatan waktu yang dinilai dengan turnaround time (dalam menit) pada masing-masing waktu tunggu (TAT) (2,3). Turnaround time sering digunakan oleh klinisi dianalisis pada pasien rawat jalan dan rawat inap.…”
unclassified
“…Hasil perhitungan waktu tunggu masing-masing tahap dengan hasil dilaporkan (3,4 Diagram fishbone digunakan untuk menentukan akar masalah pemanjangan TAT. Pada faktorman, jumlah sumber daya manusia (SDM) terutama analis kesehatan terpenuhi sesuai dengan analisis beban kerja serta standar pendidikan minimal yang telah ditetapkan.…”
unclassified
See 1 more Smart Citation